Pola Perkembangan Pendidikan Islam Pada Periodesasi Khulafa’ur Rasyidin dan Implementasinya Terhadap Perkembangan Pendidikan Islam di indonesia - Moch Faizin Muflich (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
Al-Qur'an and Sunnah are religious guidelines for Muslims who are expected to provide guidance and guide humans to a path that is blessed by Allah SWT. Every individual human must really need education. The development of Islamic education has existed since the time of Prophet Muhammad SAW until now. Education Islam was first carried out by the Prophet Muhammad SAW, namely the liberation of humans during the jahiliyah era who adhered to the heretical creed led by Quraysh groups. With an effort to free humans from all forms of oppression from one group to another group which was considered to be still weak in social status. Aqidah is one of the main values ??in an education because by implementing the values ??of faith based on aqidah and monotheism can clean the human soul that is astray, dirty to be clean and bright. during the caliphate of Abu Bakr as-Shidiq. Umar bin Khattab, Ali bin Abi Talib, Usman bin Affan. The social pattern was different during the caliphate of Abu Bakr, many regions wanted to break away from the government with the assumption that the connection with the Islamic religion no longer existed because of the death of the Prophet Muhammad SAW.